Hepatocyte-intrinsic type I interferon signaling reprograms metabolism and reveals a novel compensatory mechanism of the tryptophan-kynurenine pathway in viral hepatitis - Lercher, Alexander; Popa, Alexandra M.; Viczenczova, Csilla; Kosack, Lindsay; Klavins, Kristaps; Agerer, Benedikt; Opitz, Christiane; Lanz, Tobias; Platten, Michael; Bergthaler, Andreas (PLoS pathogens, 2020)
The liver is a central regulator of metabolic homeostasis and serum metabolite levels. Hepatocytes are the functional units of the liver parenchyma and not only responsible for turnover of biomolecules but also act as central immune signaling platforms. Hepatotropic viruses infect liver tissue, resulting in inflammatory responses, tissue damage and hepatitis. Combining well-established in vitro and in vivo model systems with transcriptomic analyses, we show that type I interferon signaling initiates a robust antiviral immune response in hepatocytes. Strikingly, we also identify IFN-I as both, sufficient and necessary, to induce wide-spread metabolic reprogramming in hepatocytes. IFN-I specifically rewired tryptophan metabolism and induced hepatic tryptophan oxidation to kynurenine via Tdo2, correlating with altered concentrations of serum metabolites upon viral infection. Infected Tdo2-deficient animals displayed elevated serum levels of tryptophan and, unexpectedly, also vast increases in the downstream immune-suppressive metabolite kynurenine. Thus, Tdo2-deficiency did not result in altered serum homeostasis of the tryptophan to kynurenine ratio during infection, which seemed to be independent of hepatocyte-intrinsic compensation via the IDO-axis. These data highlight that inflammation-induced reprogramming of systemic tryptophan metabolism is tightly regulated in viral hepatitis.